Learning Motivation in Educational Psychology: A Comparative Study between General Educational Psychology and Islamic Educational Psychology - Faiz Badridduja; Zulkipli Lessy; Eva Latipah; Subaidi Subaidi (International Journal on Advanced Science, Education, and Religion, 2022)
This article tries to uncover and unravel the essence of learning motivation from two different perspectives or starting points, namely General Educational Psychology and Islamic Educational Psychology. The purpose of writing this article is to describe the similarities and differences between these two educational psychology ideas when explaining one of the core discussions in them, that is learning motivation by comparing the both (comparison). The research method used is library research, have as a source from books and scientific journals that have a relation in this research, while the type or substancial of writing this article is descriptive comparative. The results of the main findings are that there are differences between general educational psychology and Islamic educational psychology, where western theories are only worldly and short-term, while in Islamic thoughts they are more ukhrawi or to life after death. Although both of them think that motivation has a very important role in the world of education. Keywords: Learning Motivation, Educational Psychology, Islamic Educational Psychology